THE ANALYSIS OF LANGUAGE STYLE AND THE ILLOCUTIONARY ACT FOUND IN TEEN LIT NOVEL “THE PERFECT HUSBAND” WRITTEN BY INDAH RIYANA - Nisi Nispi Rahayu; Aseptiana Parmawati (IKIP Siliwangi, 2020)
In this study described of the Language Style and Illocutionary Act that found in a teen-lit novel “The perfect Husband” Written By Indah Riyana. The methodology that used in this study is Descriptive Qualitative Method. Source of data gained from novel “The Perfect Husband”. The steps are: 1). The researchers read the novel, 2). Collecting and analyzing the sentences that consist of language style and the illocutionary act, 3). Draw the conclusion finding based on the data analysis. In this study, the Language Style found are five style but it concern to casual style because that is a teen lit novel, and the illocutionarry act that found are five categories but mostly is used of derective and expressive.Keywords: Language Style, Illocutionary Act, Teen lit novel